2016
DOI: 10.3324/haematol.2016.145060
|View full text |Cite
|
Sign up to set email alerts
|

Due to interleukin-6 type cytokine redundancy only glycoprotein 130 receptor blockade efficiently inhibits myeloma growth

Abstract: IntroductionMultiple myeloma (MM) is characterized by the expansion of clonal plasma cells within the bone marrow (BM), leading to an M-protein in serum, antibody deficiency, and skeletal destruction. Despite stem cell transplantation and novel therapies, the vast majority of patients with MM will eventually relapse and become refractory to standard therapy. Treatment strategies specifically targeting mechanisms of tumor growth and survival are being intensely explored in MM in order to improve © Ferrata Stort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…In our result, as documented also by other investigators we observed a sharp and statistically significant increase in IL-6 and TNF-α median values on days 1 and 2 after zoledronic acid infusion [19,20].…”
Section: Discussionsupporting
confidence: 79%
“…In our result, as documented also by other investigators we observed a sharp and statistically significant increase in IL-6 and TNF-α median values on days 1 and 2 after zoledronic acid infusion [19,20].…”
Section: Discussionsupporting
confidence: 79%
“…While we were unable to identify these factors, we did rule out a number of cytokines highly secreted by HS5 cells. 30 Furthermore, given that murine IL-6 does not cross-react with the human IL-6 receptor, 41 our in vivo results also suggest that other factors in the murine marrow microenvironment can stimulate JAK-STAT signaling, which is then reversed by tofacitinib. Candidates include leukemia inhibitory factor (LIF), which cross-reacts between mouse and humans, 41 , 42 or the complex between murine IL-6 and soluble murine IL-6 receptor, both of which can stimulate JAK/STAT signaling in human cells.…”
Section: Discussionmentioning
confidence: 56%
“…4b ). The pathway enrichment analysis showed that these genes are strongly associated with MM-related pathways, including the MAPK signaling pathway 38 , N-glycan biosynthesis 39 , TNF signaling pathway 40 and cytokine–cytokine receptor interaction pathway 41 (Fig. 5a ).…”
Section: Resultsmentioning
confidence: 99%